ARNÉS, Laura, DOMINGUEZ, Nora y PUNTE, María José (directoras) (2020). Historia feminista de la literatura argentina. Villa María Córdoba, Editorial EDUVIM, 592 pp. - Arnés, Laura; Domínguez, Nora; Punte, María José (Zona Franca, 2021)
ARNÉS, Laura, DOMINGUEZ, Nora y PUNTE, María José (directoras) (2020). Historia feminista de la literatura argentina. Villa María Córdoba, Editorial EDUVIM, 2020, 592 pp.